1976
DOI: 10.1210/endo-99-2-641
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Melatonin in Plasma and Urine of Pinealectomized Rats1

Abstract: Melatonin was shown to occur in rat plasma and urine after pinealectomy by bioassay, radioimmunoassay, and thin-layer chromatography. Total daily excretion of melatonin in pinealectomized rats was about 20% of control. Light-dark rhythms of plasma melatonin levels and urinary excretion rates disappeared after pinealectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
5

Year Published

1978
1978
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(62 citation statements)
references
References 0 publications
7
49
1
5
Order By: Relevance
“…A highly significant increase was seen in the dark phase, 20 h after lights on. Values are in the same range as those previously reported (Ozaki & Lynch, 1976;Pang, Brown, Grota, ) and benserazide-treated rats at 80 mg/kg (solid columns) are significant (P < 0.001-0.05); at 50 mg/kg (stippled column$) are significant (P < 0.001-0.01) except for 9 and 17 h after lights on. Significance levels were assessed by Student's t test, unpaired.…”
Section: Resultssupporting
confidence: 73%
“…A highly significant increase was seen in the dark phase, 20 h after lights on. Values are in the same range as those previously reported (Ozaki & Lynch, 1976;Pang, Brown, Grota, ) and benserazide-treated rats at 80 mg/kg (solid columns) are significant (P < 0.001-0.05); at 50 mg/kg (stippled column$) are significant (P < 0.001-0.01) except for 9 and 17 h after lights on. Significance levels were assessed by Student's t test, unpaired.…”
Section: Resultssupporting
confidence: 73%
“…within the range of the circulating levels of melatonin in rodents (Oaknin-Bendahan et al, 1992) and, therefore, could be a physiologically relevant process. Moreover, the ectopic production of melatonin by a variety of tissues is a well characterized phenomenon (Ozaki and Lynch, 1976;Kvetnoy and Yuzhakov, 1993) and may lead to local concentrations of the hormone at least one order of magnitude higher than the circulating levels (Shaw et al, 1989). The modulation by melatonin of the melanocyte response to a-MSH could be particularly strong if melatonin is produced by epidermal cells, thus increasing its concentration in the microenvironment of melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, most of the nocturnal rhythm in circulating melatonin is abolished by pinealectomy (Simonneaux and Ribelayga, 2003). However, sporadic reports suggested that as much as 20% of circulating melatonin is derived from tissues other than the pineal gland (Ozaki and Lynch, 1976).…”
Section: A Melatonin Physiology and Functionmentioning
confidence: 99%